ACCOUNTING OF BIOLOGICAL TRANSFORMATIONS IN HORTICULTURE - Hnatyshyn , Л.; Rykhlevych , А. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The text discusses the relationship between accounting methods and organizational practices in horticulture, focusing on the technological aspects of biological transformation. It defines "biological assets of horticulture" and "biological transformations in horticulture" in consideration of the economic characteristics of these assets and the processes involved in producing horticultural products. It emphasizes that biological transformation processes in horticulture can be seen as investment opportunities for agricultural enterprises, as they represent potential sources of income. Long-term biological assets in crop production are regarded as the economic natural resources of an agricultural enterprise and are utilized to generate profits or other economic benefits. Once separated from long-term biological assets and initially recognized, horticultural products are no longer considered part of biological assets and are recognized as separate assets. The text also points out that the market for horticultural products in Ukraine is not well-regulated at the legislative level, making it challenging for horticulture businesses to determine the fair value of their products. It mentions that horticultural agricultural enterprises typically evaluate their main products based on production costs, which aligns with the principle of historical (actual) cost accounting. However, given the long production cycle and modern conditions in the horticultural industry, there is a need to enhance the accounting system, particularly in primary accounting. Furthermore, the text suggests the need for proper documentation of the biological transformation process in horticulture and fruit storage to include quantitative, cost, and quality indicators. It also proposes a method for accounting for the initial cost of long-term biological assets and defines the criteria for transferring immature biological assets to the category of long-term biological assets in horticulture. Additionally, it introduces a method for accounting for biological transformation in horticulture, starting with the implementation of costs for biological transformation and concluding with the calculation of the cost price of the fruits sold.